C1 inhibitor, a multi-functional serine protease inhibitor - Davis, Alvin E., III; Lu, Fengxin; Mejia, Pedro (Thrombosis and Haemostasis, 2010)
C1 inhibitor (C1INH) is a serpin that regulates both complement and contact (kallikrein-kinin) system activation. It consists of a serpin domain that is highly homologous to other serpins and an amino terminal non-serpin mucin-like domain. Deficiency of C1INH results in hereditary angioedema, a disease characterised by episodes of angioedema of the skin or the mucosa of the gastrointestinal tract or the oropharynx. Although early data suggested that angioedema was mediated via complement system activation, the preponderance of the data indicate that bradykinin is the mediator. In the past few years, it has become apparent that C1INH has additional anti-inflammatory functions independent of protease inhibition. These include interactions with leukocytes that may result in enhanced phagocytosis, with endothelial cells via Eand P-selectins that interfere with leukocyte rolling and in turn results in suppression of transmigration of leukocytes across the endothelium, and interactions with extracellular matrix components that may serve to concentrate C1INH at sites of inflammation. In addition, C1INH suppresses gram negative sepsis and endotoxin shock, partly via direct interaction with endotoxin that interferes with its interaction with macrophages, thereby suppressing tumour necrosis factor-α and other inflammatory mediators. C1INH treatment improves outcome in a number of disease models, including sepsis and other bacterial infections, possibly malaria, ischaemia-reperfusion injury (intestinal, hepatic, muscle, cardiac, brain), hyper-acute transplant rejection, and other inflammatory disease models. Recent data suggest that this effectiveness is the result of mechanisms that do not require protease inhibition, in addition to both complement and contact system activation.
Keywords: C1 inhibitor; complement; kallikrein-kinin system; sepsis; ischaemiareperfusion injury